PENGOLAHAN LIMBAH CAIR INDUSTRI MINUMAN RINGAN - Indriyati, Indriyati; Susanto, Joko Prayitno (Jurnal Teknologi Lingkungan, 2009)
The concentration of soft drink contains organic waste water not so high. There foreone of the alternative of processing technology is used aerobic system: Oxydationditch. On this observation can be seen that the system is able to degrade theorganic matter by observe the operation parameters process to operate the systemand the parameters are BOD, COD, TSS, Oil & grease, TDS, Total N and pH. Allparameters show stability process during 3 (three) months operation. Base on thecriteria as mentioned above, the efficiency that can be reached by this system arearound 96,875 % for BOD efficiency, COD 96 % for COD efficiency , TSS 80 %, Oil& grease 75 %, Total N 76,92 % and pH 41 %.